The effectiveness of using literature response journal to improve students' writing fluency - Wendy Hiew (2010)
Writing fluency has always been one of the difficult writing skills faced by low and average proficiency students. It requires students to be able to write smoothly as the ideas flow through their mind. Even though low and average proficiency students are recommended to write freely without worrying about their spelling and grammar, they still find it hard to pen their thoughts and feelings due to the lack of vocabulary knowledge, writing practice and reading. The purpose of this study was to determine the effectiveness of using literature response journal to improve students’ writing fluency. Firstly, it utilizes the quantitative method using the quasi-experimental approach, specifically, the non-equivalent group pre-post tests design. Secondly, four factors viz. writing practice, reading habit, parental encouragement and students’ perceptions towards the English language were chosen to determine their degree of correlation with students’ writing fluency. Two groups of 30 Form Four students were systematically selected from six Form Four classes to form a control and treatment group respectively. In the treatment group, the 30 students were introduced to literature response journal and were asked to write seven journal entries, one journal each day, over seven days. Selected topics were given to the students at the end of every literature lesson. At the end of the seventh day,the total word count of each student’s journal entry was counted. The paired samples t-test was used to determine any significant difference in the total word count between Day 1 and Day 7 of the journal entries. In addition, students in the treatment group were given a four-point value Likert scale questionnaire related to their writing practice, reading habit, their parents’ encouragement in their English learning and their perception towards the English language. Each factor is correlated with their writing fluency using the Pearson Product-Moment to determine the degree of correlation. The data analysis showed a significant difference in the paired samples t-test and supports that literature response journal helps improve students’ writing fluency. Furthermore, the Pearson Product-Moment showed that students’ writing fluency had a moderate and significant correlation with their writing practice and reading habits while students’ writing fluency had a weak and no significant correlation with parental encouragement and students’ perceptions towards the English language.